Oral History in Indonesian Contemporary Historiography: A Case Study of Female Political Prisoners in Plantungan Camp 1969 – 1979 - Amurwani Dwi Lestariningsih (Diponegoro University, 2019)
In the Indonesian contemporary historiography study, the approach of oral history is important. In contemporary history, oral history is used to explore sources and collect data and facts. One of the examples is the study of Female Political Prisoners in Plantungan Camp due to the movement of 30 September 1965. Through the approach of oral history, the violence, trauma, and stigma toward female political prisoners can be revealed. This research intends to reconstruct the story of female political prisoners in Plantungan Camp, Kendal, Central Java. The Camp was formerly functioned as a concentration camp of female political prisoners who were involved in “Gerakan 30 September 1965.”